Touching Urban Spaces With Our Life. How We Experience Cities Aesthetically - Abel B. Franco (Rivista di Estetica)
I explore one distinctive aspect of our relation to spaces which is particularly significant in our everyday aesthetic evaluations of cities (urban spaces): the frequent use of linguistic expressions referring to the sense of touch. We say that a space is oppressive or expansive, or warm or cold, or (more indirectly) cozy or desolate. Touching, as involved in these expressions, seems to refer, rather than to the contact of a physical object with our skin, to a sort of touching with our life. To understand this, I try to make explicit both (a) what is being touched, i.e., the view of space behind these expressions; and (b) how and in which sense our life touches it. I propose to think about space as a plenum made of qualities (e.g., colors, smells, sounds, textures), some of which are penetrable and some of which are not. And as to how we touch spaces, I defend that we do so as we immerse ourselves in them. Once immersed in them, we are constantly both evaluating how well we fit in them as well as looking for a better-quality fitting. This is how we evaluate spaces aesthetically. Our embodied life fits better in a space when (a) we can realize more significant (for us, according to our ideal of life) possibilities in it, and (b) the felt quality of realizing those possibilities is enhanced by that space (“it feels better to read in this café”).